PENGARUH KEPERCAYAAN DAN NIAT PEMBELIAN KEMBALI TERHADAP NIAT POSITIF EWOM KONSUMEN STARBUCKS COFFEE DI JAKARTA - Hurin Hanani; Miranti Bulqis; Ady Kurniawan (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This research was conducted to ensure the influence of brand trust, OBC trust (Online brand community), and repurchase intention to positive eWOM's intentions on coffee shop (Starbucks Coffee) Customers in Jakarta. Data collection was conducted through a survey by spreading questionnaires online and obtained a sample of 152 Starbucks Coffee respondents domiciled in Jakarta. Then the data is processed, reliability and validity tests are carried out to ensure the statement indicator used is reliable and valid. Then the data is processed, reliability and validity tests arecarried out to determine the indicators of the statement applied is credible and valid. Then, the data is analyzed using the partial least squareequation model (PLS-SEM) with smartPLS 3.3 software. The results of the analysis proved that there are two of the three research hypothesessupported. The results stated that the trust of OBC (online brand community) and repurchase intentions positively influenced the intention to engagein eWOM positively. But this study is limited, one of which is a respondent who focuses on Starbucks Coffee domiciled in Jakarta, making it difficult togeneralize.